Pengaruh Komunikasi E-WOM, Konten Video, Intensitas Menonton dan Review Konsumen terhadap Keputusan Berwisata Kuliner - Lasmery RM Girsang; Ilona Vicenovie Oisina Situmeang (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The media with all its content exists to fulfill human information needs, including culinary information. In its development, social media platforms are the most active media and are frequently used in seeking and gratification to people’s information needs. On the other hand, from the culinary business side, one of the promotion tools becoming viral now is by making videos on YouTube. Consisting of food or beverage product reviews, now food vloggers dominate YouTube. Including “Mgdalenaf” YouTube which has reached 4.19 million subscribers (data as of December 24, 2022), which contains information, videos, and reviews of culinary connoisseurs regarding food products that are currently viral, delicious, and at affordable prices which are the object of this research. By using Theory of Use and Gratification, this study search for looking at relationship/influence between variables, namely E-WOM, Video Content, Watching Intensity, and Consumer Reviews on Culinary Tourism Decisions. By using simple random sampling of 100 respondents (using the Slovin formula), the results show there are influences among all variables based on classical assumption testing, linear correlation test, multiple correlation test, multiple regression, normality test, and hypothesis test T-test and F test (Cronbach Alpha value > 0.60 and sig value < 0.05). Thus, the reliability and validity were tested against 48 statement items which were responded to by all respondents